2017
DOI: 10.3389/fpsyt.2017.00164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Posttraumatic Stress Disorder in Persons with Chronic Pain: A Meta-analysis

Abstract: ObjectiveTo summarize evidence for the prevalence of posttraumatic stress disorder (PTSD) among persons with chronic pain (CP).MethodsWe searched databases for studies published between January 1995 and December 2016, reporting the prevalence of PTSD in persons with CP. Two reviewers independently extracted data and assessed the risk of bias. We calculated the pooled prevalence using a random-effects model and performed subgroup analyses according to pain location, the population and assessment method.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 60 publications
6
68
0
1
Order By: Relevance
“…Individuals with chronic pain often present with comorbid mental health problems including depression, anxiety, substance use and personality disorders (Dersh, Polatin, & Gatchel, 2002), and most commonly with high levels of depression and anxiety (Demyttenaere et al, 2007;Hooten, 2016). There is now a growing body of evidence which finds high rates of comorbidity between chronic pain, traumatic exposure and post-traumatic stress disorder (PTSD), including in individuals seeking treatment for chronic pain (Fishbain, Pulikal, Lewis, & Gao, 2017;Siqveland, Hussain, Lindstrøm, Ruud, & Hauff, 2017). Studies carried out on individuals presenting with chronic pain have found that those who have comorbid PTSD symptoms tend to have higher pre-treatment scores on measures of pain-related outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with chronic pain often present with comorbid mental health problems including depression, anxiety, substance use and personality disorders (Dersh, Polatin, & Gatchel, 2002), and most commonly with high levels of depression and anxiety (Demyttenaere et al, 2007;Hooten, 2016). There is now a growing body of evidence which finds high rates of comorbidity between chronic pain, traumatic exposure and post-traumatic stress disorder (PTSD), including in individuals seeking treatment for chronic pain (Fishbain, Pulikal, Lewis, & Gao, 2017;Siqveland, Hussain, Lindstrøm, Ruud, & Hauff, 2017). Studies carried out on individuals presenting with chronic pain have found that those who have comorbid PTSD symptoms tend to have higher pre-treatment scores on measures of pain-related outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, studies report high rates of simultaneous pain and PTSD symptomatology both in pain populations and PTSD populations [40]. Indeed, a recent meta-analysis of studies assessing PTSD symptomatology in pain samples reported a pooled mean prevalence of self-reported PTSD of 20.4% [52], indicating that a significant portion of patients with pain report clinically relevant PTSD symptomatology. PTSD symptomatology is also associated with increased levels of pain, pain-related disability, and psychological distress across pain populations [23,44,46,48,63].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PTSD seems to be strongly associated with certain conditions of chronic pain in the craniofacial segment than other conditions. In a subgroup analysis, the PTSD prevalence was higher among subjects with a headache and facial pain (9 to 25%) than in subjects with lumbar pain (0.3 to 0.7%) 29,30 . TMD patients reported traumatic stressors of different natures.…”
Section: Discussionmentioning
confidence: 82%